Existence Results for Constrained Quasivariational Inequalities. (2nd October 2013) - Motreanu, V. V.
Abstract : We deal with a constrained quasivariational inequality under a general form. We study existence of solutions in two situations depending on whether the set of constraints is bounded or possibly unbounded.